Assessment of the Effect of Urban Agriculture on Achieving a Localized Food System Centered on Chicago, IL Using Robust Optimization - Costello, Christine; Oveysi, Zeynab; Dündar, Bayram; McGarvey, Ronald; Dündar, Bayram (Amer Chemical Soc, 2021)
In this work, nonrobust (average yield) and robust (varying yield) optimization techniques were applied to find the minimum radius required from the center of Chicago, Illinois, United States (U.S.) and land area by type to meet the population's nutritional needs given yield data for conventional and urban agricultural products. Twenty-eight nutrients were considered, and land type availability was defined using satellite data. No mix of food items were able to satisfy the vitamin D, vitamin B-12, and calcium needs within a radius up to 650 km. With vitamin D fortification, radii between 175 and 185 km (nonrobust) and 205 and 220 km (robust) were found across scenarios. The inclusion of urban agriculture reduced the radius by 10-15 km and increased the diversity of foods in the solution. When vitamin B-12 was supplemented, the radii could be reduced to 105-120 km (nonrobust) and 115-130 km (robust). This work demonstrates the need to include a full list of nutrients when evaluating the feasibility of localizing food systems. Key nutrient fortification or supplementation may significantly reduce the land area required to meet the nutritional needs of a population.
Keywords: [No Keywords]